The effects of marginal glosses and online dictionary use on incidental receptive and productive vocabulary acquisition through reading - Arseven, Saliha (AUC Knowledge Fountain, 2013)
This study tests the Involvement Load Hypothesis (Hulstijn and Laufer, 2001), which suggests that incidental vocabulary acquisition depends on the involvement load (i.e. the amount of mental effort needed to complete a task) required by a task. The premise of this theory is that the use of dictionaries during reading tasks results in better vocabulary acquisition and retention than marginal glosses as the former requires more effort on the part of learners. Fifty-seven Egyptian upper intermediate ESL learners participated in this study. Half of the students were given access to an online monolingual dictionary while completing a reading comprehension task whereas the other half were provided with marginal L2 glosses. Both groups were given four uninformed immediate and four delayed vocabulary tests that measured (1) receptive knowledge of meaning, (2) productive knowledge of meaning, (3) receptive knowledge of word class, and (4) productive knowledge of word class. The results showed a superiority of the online dictionary group in productive tests while no statistically significant difference was seen between the performances of the two groups in receptive tests.